Sexual risk and transmission behaviors, partnerships and settings among young adult nonmedical opioid users in New York City - Friedman, S.R. (AIDS Behav, 2017)
BACKGROUND: Nonmedical prescription opioid use has become widespread. It can lead to heroin use, drug injection and HIV infection. We describe young adult opioid users’ sexual risk behavior, partnerships and settings. METHODS: 464 youth aged 18 – 29 who reported opioid use in the past 30 days were recruited using Respondent-Driven Sampling. Eligible participants completed a computer-assisted, interviewer-administered risk questionnaire and were tested for STIs and HIV. RESULTS: Participants (33% female; 66% white non-Hispanic) almost all had sex in the prior 90 days; 42% reported more than one partner. Same-sex sex was reported by 3% of men and 11% of women. Consistent condom use was rare. Seven percent reported group sex participation in the last 90 days but lifetime group sex was common among men and women. CONCLUSIONS: Young opioid users’ unprotected sex, multiple partners and group sex puts them and others at high HIV and STI risk.